Legal Framework and Financial Management for MSMEs in Brunei Darussalam: Challenges and Strategic Solutions - Rahmat, Diding; Istianingsih, Istianingsih (Greenation Research & Yayasan Global Resarch National, 2024)
Effective financial management is a key factor for the success and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Brunei Darussalam. This article explores the implementation of a legal framework for financial management among MSMEs and examines the challenges encountered in the regulatory implementation process. Using a descriptive-qualitative approach, the study analyzes the financial regulations applied in Brunei and their impact on the financial and legal literacy of MSME actors. The findings indicate that although the financial regulations in Brunei have been comprehensively designed, there remains a significant gap between the formulated policies and their implementation. The low levels of financial and legal literacy among MSME actors, coupled with a lack of support from regulators, exacerbate non-compliance with existing regulations. This article recommends simplifying regulations, enhancing financial and legal literacy programs, and strengthening the role of regulators as facilitators to ensure that MSMEs can more easily understand and comply with their legal obligations. Through regulatory harmonization and improved literacy, MSMEs in Brunei are expected to become more competitive and capable of accessing broader financing opportunities to support business growth.